2018
DOI: 10.3390/en11030660
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Model Prediction for Demand Forecast in Water Distribution Networks

Abstract: This paper presents a multi-model predictor called Qualitative Multi-Model Predictor Plus (QMMP+) for demand forecast in water distribution networks. QMMP+ is based on the decomposition of the quantitative and qualitative information of the time-series. The quantitative component (i.e., the daily consumption prediction) is forecasted and the pattern mode estimated using a Nearest Neighbor (NN) classifier and a Calendar. The patterns are updated via a simple Moving Average scheme. The NN classifier and the Cale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The water consumption dataset is categorized into the training and validation datasets for forecasting water demand. In general, the training dataset uses the entire observed values of 70-90%; however, in this study, among the water consumption data of one year measured at one-hour intervals, 70% of the data were used as the training dataset overtime sequence, whereas the remaining 30% were used as the validation dataset [31]. The water consumption data are standardized for reducing the bias in demand forecasting.…”
Section: Study Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The water consumption dataset is categorized into the training and validation datasets for forecasting water demand. In general, the training dataset uses the entire observed values of 70-90%; however, in this study, among the water consumption data of one year measured at one-hour intervals, 70% of the data were used as the training dataset overtime sequence, whereas the remaining 30% were used as the validation dataset [31]. The water consumption data are standardized for reducing the bias in demand forecasting.…”
Section: Study Processmentioning
confidence: 99%
“…Rangel et al [29] used the concept of daily water consumption pattern predicted based on Nearest Neighbor (NN) node estimation, which is a nonparametric method; Cheifetz et al [30] estimated the water demand pattern for each day of the week using the hourly water consumption data based on the Fourier regression mixture model. Particularly, Farias et al [31] applied the NN classification, which is an ML model, and a calendar effect based on quantitative and qualitative information, and proposed the Qualitative Multi-Model Predictor Plus (QMMP+) model for estimating water demand patterns based on the moving average (MA). Here, better results were produced when the total daily water demand was forecasted using the SARIMA model applied with a sliding window [26], whereas the hourly water demand was distributed with the NN model according to a calendar effect for daily patterns and compared with the ANN model.…”
Section: Introductionmentioning
confidence: 99%
“…Their study results were found to be satisfactory in a comparison with other used techniques in the literature. In addition, Farias, Puig, Rangel and Flores [25] attempted to forecast the demand of water distribution networks by deploying a multi-model predictor, qualitative multi-model predictor plus (QMMP+). In their study, it was found that such a predictor enhances the forecasting precision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An operational MPC approach was proposed by Pascual et al [6], tasked with reducing costs, as well as maintaining safety storage volumes in the buffer tanks. Another control based water management system was proposed by Lopez Farias et al [7]. In this case, the forecasting accuracy of the control system was improved by means of a qualitative multi-model predictor.…”
Section: Introductionmentioning
confidence: 99%